2014
DOI: 10.1155/2014/160316
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Recombinant Schmallenberg Virus Nucleocapsid Protein in Yeast and Development of Virus-Specific Monoclonal Antibodies

Abstract: Schmallenberg virus (SBV), discovered in continental Europe in late 2011, causes mild clinical signs in adult ruminants, including diarrhoea and reduced milk yield. However, fetal infection can lead to severe malformation in newborn offspring. To develop improved reagents for SBV serology, a high-level yeast expression system was employed to produce recombinant SBV nucleocapsid (N) protein. Recombinant SBV N protein was investigated as an antigen in SBV-specific IgG enzyme immunoassay and used for generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The sensitivity of 96 % for serum IgG assay compared to commercial serum IgG ELISA was achieved. This shows a slight improvement over our recently developed indirect serum anti-SBV IgG ELISA [ 16 ], where the sensitivity of the assay was 95 %. A low degree of correlation between optical densities of the same serum samples in commercial and our tests was observed and may suggest that different epitopes on the nucleocapsid protein are recognized in these assays.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The sensitivity of 96 % for serum IgG assay compared to commercial serum IgG ELISA was achieved. This shows a slight improvement over our recently developed indirect serum anti-SBV IgG ELISA [ 16 ], where the sensitivity of the assay was 95 %. A low degree of correlation between optical densities of the same serum samples in commercial and our tests was observed and may suggest that different epitopes on the nucleocapsid protein are recognized in these assays.…”
Section: Discussionmentioning
confidence: 75%
“…The cloning of the SBV N gene and purification under denaturing conditions of the recombinant SBV N antigen was recently described [ 16 ]. Our recent findings indicated that the SBV N protein purified under native conditions exhibited better antigenicity than the SBV N protein purified under denaturing conditions (See Additional file 1 : Figure S1 and Additional file 2 : Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, past infections would have been shown by antibody tests. Because bunyaviruses from all vertebrate-infecting genera induce antibodies against the nucleoprotein ( 12 14 ), we are confident about our choice of antigen in our assays. Chung et al presented no serologic results to support virus detections ( 9 ).…”
Section: The Studymentioning
confidence: 99%
“…Although the mechanism of overwintering is not known until now and despite a very high seroprevalence of approximately 70% to nearly 100% in ruminants in the initially most affected areas [ 6 , 7 , 8 ], SBV re-appeared in the following vector season [ 9 ]. In 2012, SBV spread across the British Isles to Scotland and Ireland [ 10 , 11 , 12 , 13 , 14 ], reached the Scandinavian countries [ 15 , 16 , 17 ] and Eastern Europe as far as Lithuania [ 18 ], crossed the Alps [ 19 , 20 ], and spread to the Mediterranean area [ 21 , 22 ]. Thus, the virus was detected Europe-wide only 1 year after its initial discovery [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%